Post-Traumatic Growth Among Patients Suffering From Burn: A Cross-Sectional Study - Alimour, Shirin Abdallah; Aljasmi, Shaima; Alnono, Mhd Emad; Alaji, Nouha; El Farran, Hani; Alrabeei, Mohamed Mahmoud (National Journal of Community Medicine, 2024)
Background: Burn and wounds are one of the most serious hospital cases in all healthcare settings, both social and psychological support are needed to overcome all depressive and anxious feelings afterward the burns' incidence. This study aims to assess and evaluate all posttraumatic growth experiences from healthcare professionals after burns and wounds on selected patients with various degrees of burns. Methods: It was a cross-sectional descriptive design. The present study utilized regression analysis as a statistical tool to examine the variables linked to posttraumatic growth in a sample of 191 individuals who had undergone significant burn injuries. Results: The study revealed that those undergoing therapy for mild depression exhibited a modest degree of depressive symptoms and a diminished feeling of positive self-perception compared to those in the acute phase. Therefore, a statistically significant difference in the averages was noticed between the two groups. An important correlation was found between depressive symptoms and social support, which had a significant impact on posttraumatic growth during the recovery phase. Conclusions: The present study revealed that social support exerted a noteworthy influence in promoting posttraumatic growth among individuals belonging to the acute phase group.